1975
DOI: 10.1002/ijc.2910150408
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by drugs of metastatic lung nodule formation after intravenous tumour cell injection

Abstract: In studies on a model of induced pulmonary metastasis in mice a tumour host system was analysed which was not affected by immunogenicity of the tumour for the host; neither intensive immunosuppression nor immunization caused a significant change in the quantity of pulmonary metastatic nodules. In contrast the application of cytostatic drugs and of Corynebacterium parvum could modify the pulmonary resistance to the formation of tumour nodules by a factor greater than 100 in either direction. This finding confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 15 publications
2
44
0
Order By: Relevance
“…Three cytotoxic agents were investigated for their ability to enhance lung colony formation by the Lewis lung tumour: cyclophosphamide (CY) (the agent that in the hands of van Putten et al (1975) gave the greatest enhancement with the C22LR osteosarcoma) local thoracic or whole-body irradiation (found by Brown (1973) to enhance colony formation by the KHT sarcoma) and bleomycin (because of its tendency to enhance radiation-induced lung damage). The experiments were designed to measure the "enhancement factor" due to pretreatment of the recipient mice (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three cytotoxic agents were investigated for their ability to enhance lung colony formation by the Lewis lung tumour: cyclophosphamide (CY) (the agent that in the hands of van Putten et al (1975) gave the greatest enhancement with the C22LR osteosarcoma) local thoracic or whole-body irradiation (found by Brown (1973) to enhance colony formation by the KHT sarcoma) and bleomycin (because of its tendency to enhance radiation-induced lung damage). The experiments were designed to measure the "enhancement factor" due to pretreatment of the recipient mice (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…injected cells has been used as a method of assaying the clonogenic capacity of cells removed from treated murine tumours. This approach was first described by Hill and Bush (1969) using the KHT sarcoma, and since that time it has been applied to a number of other mouse tumouirs including the C22LR osteosarcoma (van Putten et al, 1975) and the Lewis lung tumour and B 16 melanoma (Hill and Stanley, 1975). A high cloning efficiency in the lungs for i.v.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 Using the method of Teicher et al, 27 Mitsumoto et al 30 established 2 CPTresistant mouse epithelial tumour cell lines with enhanced metastatic capabilities associated with higher levels of cell adhesion to ECM components, such as fibronectin, laminin, collagen type IV and Matrigel; enhanced MMP-2 activity; and higher levels of cell motility. Van Putten et al 31 showed that treatment of animals bearing a transplantable osteosarcoma with cyclophosphamide or CCNU resulted in a significant increase in lung metastases compared to controls. Following these initial observations, enhancement of metastases was also obtained in other tumour systems with cyclophosphamide 32,33 and bleomycin.…”
Section: Discussionmentioning
confidence: 99%
“…He thus proved that reduction of TD50 for tumour cells, in mice recently exposed to WBI, was not, in this case, an immunological phenomenon. Van Putten et al (1975) demonstrated a significant decrease of RNM and increase of pulmonary metastasis, following intratesticular injection of non-immunogenic sarcoma cells, if the mice received a single dose (250 mg/kg) of cyclophosphamide 2 h after injection of tumour. In their system, pre-exposure of mice to WBI increased pulmonary metastases but not RNM (a notable distinction from our finding).…”
Section: Discussionmentioning
confidence: 99%